White guava (Psidium guajava L.) fruit juice ameliorated the number of spermatogenic cells in rats (Rattus Novergicus) exposed to lead acetate - Muhammad Faizal Adiutomo; Suzanita Utama; Herry Agoes Hermadi; Wurlina Wurlina; Hardany Primarizky; Rochmah Kurnijasanti (Universitas Airlangga, 2024)
This study aims to determine the effect of oral administration of white guava fruit juice (Psidium guajava L.) on the spermatogenic cells of rats (Rattus norvegicus) exposed orally to lead acetate. Twenty-five male rats (Rattus norvegicus) of the Wistar strain were randomly divided into five groups. Placebo group rats (P0) were given 0.5 mL distilled water twice every day orally at four-hour intervals. Groups T0, T1, T2, and T3 were given lead acetate 50 mg/kg bw orally, then respectively given distilled water, 100, 50 and 25% (v/v) white guava (Psidium guajava L.) fruit juice orally four hours later for 14 days. On day-15, the rats were sacrificed and their testicles were taken for histological preparations. Data were analyzed using Analysis of Variance followed by Duncan's Multiple Range Test. The results showed that the number of spermatogonia, spermatocytes and spermatids cells of rats in T0 group was lower (p <0.05) than in P0 group. Higher spermatogonia, spermatocytes and spermatids cells (p <0.05) were found in the T1 group compared to the T0 group. However, the number of spermatogonia and spermatocytes in the T1 group was still lower than in the P0 group. The number of spermatids in the T3 group was almost the same (p >0.05) as in the P0 group. This study found that white guava pure juice without dilution was the best for maintaining the number of spermatids, but was unable to restore the number of spermatogonia and spermatocyte cells in rats exposed to lead acetate.